Ð’Ð¿Ð»Ð¸Ð² Ñ‚ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€ Ð·Ð±ÐµÑ€Ñ–Ð³Ð°Ð½Ð½Ñ Ð½Ð° Ð¶Ð¸Ñ‚Ñ‚Ñ”Ð·Ð´Ð°Ñ‚Ð½Ñ–ÑÑ‚ÑŒ ÐºÐ»Ñ–Ñ‚Ð¸Ð½ Escherichia coli Ðœ-17 - Dorofeyeva, Tatyana V.; Kudokotseva, Olga V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2015)
N/A